2020
DOI: 10.3390/ma13092054
|View full text |Cite
|
Sign up to set email alerts
|

Highly Defective Dark Nano Titanium Dioxide: Preparation via Pulsed Laser Ablation and Application

Abstract: The development of methods to synthesize and study the properties of dark titania is of the utmost interest due to prospects for its use, primarily in photocatalysis when excited by visible light. In this work, the dark titania powder was prepared by pulsed laser ablation (Nd:YAG laser, 1064 nm, 7 ns) in water and dried in air. To study the changes occurring in the material, the thermal treatment was applied. The structure, composition, and properties of the obtained powders were studied using transmission ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 74 publications
(112 reference statements)
0
23
0
Order By: Relevance
“…The LAL method leads to the formation of the dispersed particles with a defective, distorted structure. [38][39][40][41] As the defects of the TiO2 support might stimulate the metal-support interaction, [42][43][44] the LAL can be a promising method for the preparation of the Pt/TiO2 catalysts active in the ammonia oxidation reaction. Previously, it was shown that the composites prepared by LAL are active in CO oxidation reaction, 38,39 low-temperature ammonia oxidation, 45 phenol photodegradation process under visible light.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LAL method leads to the formation of the dispersed particles with a defective, distorted structure. [38][39][40][41] As the defects of the TiO2 support might stimulate the metal-support interaction, [42][43][44] the LAL can be a promising method for the preparation of the Pt/TiO2 catalysts active in the ammonia oxidation reaction. Previously, it was shown that the composites prepared by LAL are active in CO oxidation reaction, 38,39 low-temperature ammonia oxidation, 45 phenol photodegradation process under visible light.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was shown that the composites prepared by LAL are active in CO oxidation reaction, 38,39 low-temperature ammonia oxidation, 45 phenol photodegradation process under visible light. 41 The supported Pt/TiO2 catalysts were studied using NAP-XPS and operando XAS -powerful complementary tools for the investigation of the catalysts under working conditions. The application of these methods provided insights into the evolution of the surface and bulk Pt particle structure under NH3+O2 conditions showing that the metal platinum particles do not undergo significant oxidation under the reaction conditions, regardless of the preparation method.…”
Section: Introductionmentioning
confidence: 99%
“…In Refs. [ 45 , 46 ], we obtained dark titania by nanosecond PLAL in distilled water. It features an intense absorption in the visible region of the spectrum caused by the presence of defects of various nature, and exhibits increased photocatalytic activity in the decomposition of the dye Rhodamine B and phenol, as well as an antibacterial effect against S. Aureus and E. Coli [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…1), sulfides, carbides, etc. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. In this approach, laser beam is typically focused on a solid target, its pulses ablating the target and producing various nanostructures whose morphology, size and chemistry depend on the laser pulse parameters and liquid medium [14][15][16][18][19][20][21]25,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. In this approach, laser beam is typically focused on a solid target, its pulses ablating the target and producing various nanostructures whose morphology, size and chemistry depend on the laser pulse parameters and liquid medium [14][15][16][18][19][20][21]25,29,30]. As a preparative method, LAL is attractive for several reasons: (i) it is an easy-to-use and green technique consuming minimum chemicals; (ii) a wide variety of nanostructures can be prepared, with control over their composition and morphology; (iii) the method operates at nominally room temperature while can often generate unique phases and morphologies.…”
Section: Introductionmentioning
confidence: 99%